A Rare Case of Perioperative Methemoglobinemia in a Paediatric Child: A Case Report - Mohamad Azlan Awang; Muhamad Rafiqi Hehsan (Universiti Putera Malaysia, 2024)
Methemoglobinemia is a rare condition that caused impairment of oxygen delivery manifested as spectrum of features ranging from mild desaturations to severe cyanosis and even death. It is rarely seen in the operative theatre and its incidence is scarcely reported. Even low risk patients are susceptible despite having no significant exposure to commonly reported precipitating oxidizing agents. We described a case of perioperative methemoglobinemia in a 10-year-old child, which was planned for foreign body removal in left ear. The operation went successfully; however, the child developed desaturation postoperatively. Arterial blood gas was measured, and methemoglobin levels were noticeably high at 27.1%. The child remained hemodynamically stable, monitored conservatively, and was successfully treated with intravenous methylene blue. We postulated that the cause of methemoglobinemia was intravenous fentanyl usage, as other oxidising agents were excluded. Clinicians must be aware of the possibility of perioperative methemoglobinemia causing unanticipated desaturations and unexplained cyanosis.